Preeclampsia is associated with an increased pro-inflammatory profile in newborns. (November 2015) - Guillemette, Laetitia; Lacroix, Marilyn; Allard, Catherine; Patenaude, Julie; Battista, Marie-Claude; Doyon, Myriam; Moreau, Julie; Ménard, Julie; Ardilouze, Jean-Luc; Perron, Patrice; Côté, Anne-Marie; Hivert, Marie-France
Highlights: We phenotyped a prospective population-based cohort of pregnant women. We carefully distinguished gestational hypertension from preeclampsia. TNFα is elevated in the umbilical cord blood of newborns exposed to preeclampsia. This inflammatory profile is independent of confounders. Abstract: Hypertensive disorders of pregnancy (HDP) lead to high rates of maternal and fetal morbidity. Existing studies on inflammatory marker TNFα in HDP offspring are inconsistent. We performed a population-based cohort study of 636 pregnancies, including normotensive (NT) women and women with preeclampsia (PE) or gestational hypertension (GH). TNFα was measured in maternal blood in the first and second trimesters and in cord blood at the time of delivery. Cord blood TNFα was higher in offspring delivered of women with PE (6.53 [4.94–8.38]pg/mL) versus those delivered of NT women (5.13 [4.11–6.72]pg/mL; p = 0.01), independent of confounders. Maternal TNFα levels were not different among groups ( p > 0.1) in either the first or second trimester.